Cardiopulmonary Exercise Test: Applications and Interpretation - Dey, Pulak Kumar; Bhowmik, Mita; Kar, Sanjoy Kumar; Gain, Subrata Kumar (Chest & Heart Journal, 2021)
Cardiopulmonary exercise test (CPET) is often an overlooked and underutilized modality but offers an ocean of information about a patient’s functional status. The following parameters are measured: ventilation; oxygen consumption (VO2); carbon dioxide production (VCO2); and the other variables of conventional exercise testing. The CPET allows defining mechanisms related to low functional capacity that can cause symptoms, such as dyspnoea, and correlate them with changes in the cardiovascular, pulmonary and skeletal muscle systems. Indications include evaluation of dyspnea, distinguishing cardiac vs pulmonary vs peripheral limitation vs others and detection of exercise-induced bronchoconstriction. Exercise modalities are cycle ergometer and treadmill. In heart disease breathing reserve is >30%, and heart rate reserve is <15%, in pulmonary disease breathing reserve is <30% but heart rate reserve is >15%. Chest Heart J. 2020; 44(2) : 100-105